Analysis Effectiveness Advertisement Bank Sharia Indonesia Through Network Social Instagram as a Promotional Media - Icha Rosmeisya; Dewi Manda Angraini (AL-ARBAH: Journal of Islamic Finance and Banking, 2025)
Purpose - This study aims to analyze the effectiveness of Bank Syariah Indonesia (BSI) advertisements through Instagram as a promotional medium among Islamic Banking students, Class of 2021, UIN Bukittinggi. The research is motivated by the rapid growth of digital platforms that require companies to be more creative in marketing products. Method - A descriptive qualitative approach was applied using the AIDA (Attention, Interest, Desire, Action) model. Data were collected through in-depth interviews with students of the Islamic Banking Class of 2021. Result - The findings indicate that the effectiveness of BSI advertisements on Instagram varies across the AIDA stages. At the Attention stage, ads were very effective, with 100% of respondents having seen them. At the Interest stage, ads were considered effective by 70% of respondents. At the Desire stage, only 50% were motivated to seek further information, mainly due to promotional offers. At the Action stage, effectiveness was low, with only 30% engaging directly through likes or shares. Implication - The study suggests BSI should optimize Instagram strategies by enhancing emotional appeal, unique messages, and interactive tactics to encourage real actions. Originality - This research highlights the evaluation of Islamic bank advertising effectiveness using the AIDA model, focusing on student perceptions as an important target segment. Keywords: AIDA, advertising effectiveness, Instagram, Islamic banking, Bank Syariah Indonesia.